Does Shareholder Concentration Matter In Small And Medium Enterprises (SMES)? Empirical Evidence From SMES In Manufacturing Sector In Northern Corridor Economic Region (NCER). - Lim, Kent Soon (2009)
Given the important role of SMEs as a growth factor in local economy, ensuring a strong and competitive development for this industry segment has become a key concern in making the Northern Corridor Economic Region (NCER) a success. This study investigates the effects of shareholder concentration, together with financial inputs and outputs on the relative operating efficiency in utilization of financial resource (financial efficiency) for SMEs in manufacturing sector in NCER for the financial year 2007. The financial efficiency is derived from Data Envelopment Analysis (DEA). DEA shows that only 27 SMEs scored 100% efficiency, and they are mostly from Penang and Perak. This study delivers three important findings: first, shareholder concentration does affect the financial efficiency for SMEs involved in manufacturing sector in NCER; second, lower financial inputs and higher financial outputs produce higher financial efficiency SMEs involved in manufacturing sector in NCER; third, the distribution of financial efficiency is not balance across the three states in NCER. The last point is consistent with the Korean case reported in Yang (2006).